2021
DOI: 10.1007/s10815-021-02176-3
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal markers as noninvasive predictors of sperm retrieval in non-obstructive azoospermia

Abstract: Non-obstructive azoospermia (NOA) is one of the leading causes of male factor infertility, which results from impaired spermatogenesis. Currently, the sole feasible therapeutic option for men with NOA to father their biologic children is sperm retrieval by testicular sperm extraction (TESE) approaches followed by an intracytoplasmic sperm injection program. Nevertheless, the rate of sperm retrieval from NOA men following TESE has remained as low as 50%, leading to a significant number of unsuccessful TESE oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Zarezadeh et al. also found that both serum hormones and semen hormones have advantages and disadvantages in predicting spermatogenesis in patients with NOA ( 33 ). There may be some relationship between them, but there are significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…Zarezadeh et al. also found that both serum hormones and semen hormones have advantages and disadvantages in predicting spermatogenesis in patients with NOA ( 33 ). There may be some relationship between them, but there are significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…The quality assessment of the selected studies was independently completed by two reviewers (Junjun Li and Xujun Yu). Studies were then classified according to their quality into poor (0-4), moderate (5)(6), or high quality (7)(8)(9).…”
Section: Methodsmentioning
confidence: 99%
“…Successful sperm retrieval (SSR) is defined as obtaining at least one spermatozoon via surgical testicular sperm extraction [ 6 ]. Although the value of serum hormonal markers in predicting SSR was expected, the research results were unsatisfactory [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous investigations have demonstrated that the success of micro-TESE cannot yet be predicted by current reproductive hormones, age, testicular volume, or testicular disease diagnosis [ 3 , 8 , 9 ]. The predictive usefulness of the relevant preoperative markers remains equivocal [ 10 ].…”
Section: Introductionmentioning
confidence: 99%